(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The efficient government finance will increase economic growth and thereby income distribution. This research has been formulated an efficiency theory of production and finance. This research compared the government expenditure patterns into two situations. One, when a government borrows and accordingly allocates resources for productive expenditures for private and public finance. Another situation is that when a government borrows and fixed the resources for productive expenditure for only public finance. A comparative efficiency theory of production and finance are being formulated to test the general equilibrium of production of goods and services. This general equilibrium theory of efficient production of a firm has been made a conclusion that government resource allocation in both for private and public finance is efficient and never creates economic distortion even if these resources are borrowed form domestic sources. These domestic sources might be private commercials banks or any other financial institutions. The government resource allocation is not efficient when the government borrowing is fixed only for increasing public finance. This process implies diminishing return and thus increases public expenditure implicitly. Increasing nonproductive government expenditure will expand the size of the government and accordingly reduce economic growth in the long run. But both the private and public finance from borrowing will not hamper the efficiency of the production of a firm and accordingly reduce economic distortion. The tendency of reducing economic distortion will ultimately increase economic growth and economic welfare as well. Keywords: Finance; Government Expenditure DOI: 10.3329/jbau.v7i2.4748 J. Bangladesh Agril. Univ. 7(2): 367-371, 2009